Smoking Status and Functional Outcomes in Young Stroke - Liang, Cheng-Loong; Chen, Han-Jung; Lee, Yi-Che; Wu, Cheng-Chun; Tsai, Chon-Haw; Chen, Po-Lin; Chang, Wei-Lun; Yeh, Po-Yen; Wei, Cheng-Yu; Tsai, Ming-Jun; Sun, Yu; Lin, Chih-Hao; et al. (Frontiers in Neurology, 2021)
Objective: Stroke in young adults is uncommon, and the etiologies and risk factors of stroke in young adults differ from those in the older populations. Smoker’s paradox is an unexpected favorable outcome, and age difference was used to explain the association between smoking and the favorable functional outcome. This study aimed to investigate the existence of this phenomenon in young stroke patients. Methods: We analyzed a total of 9,087 young stroke cases registered in the nationwide stroke registry system of Taiwan between 2006 and 2016. Smoking criteria included having a current history of smoking more than 1 cigarette per day for more than 6 months. After matching for sex and age, a Cox model was used to compare mortality and function outcomes between smokers and non-smokers. Results: Compared with the non-smoker group, smoking was associated with older age, higher comorbidities, and higher alcohol consumption. Patients who report smoking with NIHSS scores of 11–15 had a worse functional outcome (adjusted OR, 0.81; 95% CI, 0.76–0.87). Conclusion: Smokers had a higher risk of unfavorable functional outcomes at 3 months after stroke, and therefore we continue to strongly advocate the importance of smoking cessation.